2019
DOI: 10.1161/jaha.118.009056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiovascular Health Between US Army and Civilians

Abstract: Background Cardiovascular conditions are common in US Army and civilian populations. The recently developed concept of ideal cardiovascular health provides a new approach to evaluating population cardiovascular status. Methods and Results We defined a cohort of 263 430 active duty Army personnel, aged 17 to 64 years, who completed a 2012 physical examination and a corresponding subset of the noninstitutionalized, civilian US population, who participated in the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…For example, one study ( n = 303 223; mean age 31 years) reported 15.6% prevalence of hypertension among U.S. veterans with a mental health diagnosis excluding PTSD and 30.8% prevalence among those with PTSD with or without another mental health diagnosis (Cohen et al ., 2009). In a cross-sectional study also drawing on data from active-duty U.S. Army soldiers but weighted to the 2012 U.S. Army active-duty population, 5% of soldiers were estimated to have hypertension and 64.7% were estimated to be pre-hypertensive at the time of assessment in 2012 (Shrestha et al ., 2019). Thus, findings from this sample do support the notion that individuals in the military are at higher risk of developing hypertension relatively early in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study ( n = 303 223; mean age 31 years) reported 15.6% prevalence of hypertension among U.S. veterans with a mental health diagnosis excluding PTSD and 30.8% prevalence among those with PTSD with or without another mental health diagnosis (Cohen et al ., 2009). In a cross-sectional study also drawing on data from active-duty U.S. Army soldiers but weighted to the 2012 U.S. Army active-duty population, 5% of soldiers were estimated to have hypertension and 64.7% were estimated to be pre-hypertensive at the time of assessment in 2012 (Shrestha et al ., 2019). Thus, findings from this sample do support the notion that individuals in the military are at higher risk of developing hypertension relatively early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if age-related increases in blood pressure could be prevented or lessened, the burden of CVD might be substantially reduced (Rieder, 2007; Institute of Medicine, 2010). Certain populations have also been identified as having elevated risk of developing hypertension relatively early in life, including those exposed to major occupational stressors, like service members and veterans (Yu et al ., 2003; Shrestha et al ., 2019). Besides occupational status, other sociodemographic correlates of high blood pressure have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…A diagnosis of high blood pressure for, example, was established in 18% of cases, similar to our results (19.51%). Preventive health interventions aimed at blood pressure regulation of service members through physical activity and nutrition may provide significant improvements in cardiovascular health not only for the active military personnel but also in civilians (13,25). In addition to the health care status of the military personnel, reduction of the health care costs is also very important for each national army force.…”
Section: Discussionmentioning
confidence: 99%
“…Among included studies (26 cross-sectional and four cohort studies), 11 studies conducted in India [7,8,[17][18][19][20][21][22][23][24][25], four in the USA [26][27][28][29], two in Iran [30,31], two in Saudi Arabia [32,33], one in Brazil [34], one in Sweden [35], one in Canada [36], one in Poland [37], one in Zambia [38], one in Jordan [39], one in Guinea-Bissau [40], one in Thailand [41], one in Brunei [42], one in Sri Lanka [43], and one in Ethiopia [6], with report of diabetes (n = 30) and prediabetes (n = 9) prevalence. Studies participants consisted of military personnel, soldiers, and conscripts, as well as police personnel and o cer.…”
Section: Description Of Studiesmentioning
confidence: 99%